SELF REFERENCE AND ITS VARIATION AMONG THE TEENAGERS - Siti Aisyah (EKSPOLHUM, 2024)
This research applied a descriptive qualitative method. The study was applied to describe how the teenager use self-reference in different contexts or situations and to find out whether or not gender influences the use of self-reference and  also the reasons. The data was taken from  the utterances of the teenager in their daily conversation. In this research the source of the data was the teenagers that included six males and six females with an age range of 14-18 years old.  Based on the empirical data, there are three kinds of Self- References the reseacher found in this study. They are proper name (such as Zati, Iki, Bella, Agri), kinship term (uni means kakak and uda means abang) and formality term (saya, awak and aku). Then, the data also showed that female more prefer addressed their self in form of proper name eventhough the situation formal or informal. While male more prefer addressed their self in form of awak or aku even it formal or infomal.  The following figure showed the number of the form of self-reference used by the teenagers.